Phytochemicals and bioactivities of Artocarpus Anisophylluss MIQ - Jema'on, Noraini (2013)
Phytochemicals and bioactivities of the heartwood and stem bark of Artocarpus anisophyllus Miq. have been studied. Extraction of the air-dried and powdered form of both parts was carried out by cold extraction method using n-hexane, dichloromethane and ethyl acetate as the solvent system. Fractionation and purification of the crude extracts have resulted in the isolation of eight compounds including flavonoids, triterpenes and a plant sterol. A new compound was isolated from the heartwood of A. anisophyllus which was identified as 3?-hydroxycycloartocarpin together with chaplashin, cycloartocarpin, artocarpin, derivative of artoindonesianin Z-1, a mixture of stigmast-4-en-3-one and stigmasta-4,22-dien-3-one, and ß-sitosterol. The last compound, 6-hydroxystigmast-4-en-3-one was isolated from the stem bark of A. anisophyllus, together with derivative of artoindonesianin Z-1 which previously isolated from the heartwood. Their structures were elucidated using spectroscopic methods including Nuclear Magnetic Resonance, Infrared, Ultraviolet spectroscopies and Mass spectrometry. Bioactivities were carried out on the crude extracts and pure compounds. The antibacterial test on the crude extracts and pure compounds were carried out against the Gram-positive bacteria, Bacillus subtilis and Staphylococcus aureus and Gramnegative bacteria, Escherichia coli and Pseudomonas aeruginosa. The most significant antibacterial activity was shown by the dichloromethane extract of the heartwood against E. coli with the MIC value of 125 µg/mL. Artocarpin showed moderate antibacterial activity against B. subtilis and E. coli with MIC value of 250 µg/mL. Derivative of artoindonesianin Z-1 showed significant antibacterial activity against B. subtilis with MIC value of 250 µg/mL. The antioxidant assay using DPPH radical showed that the dichloromethane extract of the stem bark of A. anisophyllus possessed the highest radical scavenging activity with IC50 value of 307.24 µg/mL. Among the pure compounds tested, artocarpin showed the strongest radical scavenging property with IC50 value of 69.63 µg/ml.